2017
DOI: 10.1080/10503307.2017.1292067
|View full text |Cite
|
Sign up to set email alerts
|

Therapists’ honesty, humor styles, playfulness, and creativity as outcome predictors: A retrospective study of the therapist effect

Abstract: Therapists' inferred traits of Honesty-Humility and AHS may influence the effectiveness of their treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 53 publications
2
31
1
1
Order By: Relevance
“…The naturalistic setting was most commonly adopted (73.33%, k = 22). Of the studies that used this research design, 18 (81.82%) reported an average length of 25.78 sessions ( SD = 11.78, Mdn = 23.5), 1 (4.54%; Talley, Strupp, & Morey, ) reported a length ranging from 4 to 25 sessions, 1 (4.54%; Yonatan‐Leus, Tishby, Shefler, & Wiseman, ) reported a length of 1 year, and 2 (9.10%; Williams & Fauth, ; Wongpakaran & Wongpakaran, ) did not report treatment duration. Three studies (10%; Anderson, McClintock, Himawan, Song, & Patterson, ; Schauenburg et al, ; Wiseman & Tishby, ) used a longitudinal design with an average length of 18.03 sessions ( SD = 12.13, Mdn = 12.01).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The naturalistic setting was most commonly adopted (73.33%, k = 22). Of the studies that used this research design, 18 (81.82%) reported an average length of 25.78 sessions ( SD = 11.78, Mdn = 23.5), 1 (4.54%; Talley, Strupp, & Morey, ) reported a length ranging from 4 to 25 sessions, 1 (4.54%; Yonatan‐Leus, Tishby, Shefler, & Wiseman, ) reported a length of 1 year, and 2 (9.10%; Williams & Fauth, ; Wongpakaran & Wongpakaran, ) did not report treatment duration. Three studies (10%; Anderson, McClintock, Himawan, Song, & Patterson, ; Schauenburg et al, ; Wiseman & Tishby, ) used a longitudinal design with an average length of 18.03 sessions ( SD = 12.13, Mdn = 12.01).…”
Section: Resultsmentioning
confidence: 99%
“…The 1,289 therapists who participated in the study were predominantly female (66.41%, n = 856). Only nine studies (30%; Anderson, Ogles, Patterson, Lambert, & Vermeersch, ; Anderson et al, ; Hilliard et al, ; Kaplowitz, Safran, & Muran, ; Lawson & Brossart, ; Najavits & Strupp, ; Talley et al, ; Williams & Fauth, ; Wiseman & Tishby, ; Yonatan‐Leus et al, ) reported therapists' ethnicity; of the 225 therapists in these studies, 158 were White/Caucasian (70.22%), 41 were Israeli (18.22%), 6 were Asian American (2.67%), 4 were Black/African American (1.78%), 2 were Native American (0.89%), 2 were Hispanic/Latino (0.89%), and the remaining 12 (5.33%) did not declare their ethnicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ιδιαίτερη δε σημασία φαίνεται να κατέχει μια ακόμη ωριμοποιός διάσταση της πρωταρχικής αλληλεπίδρασης μητέρας-βρέφους, όπως αυτή μεταφέρεται ως δυναμική λειτουργία στο πλαίσιο της θεραπευτικής σχέσης (Winnicott, 1971), «η ικανότητα του θεραπευτή για παιχνίδι» (playfulness). Η συγκεκριμένη δεξιότητα, η οποία έχει τύχει περιορισμένης εμπειρικής μελέτης έως σήμερα (Yonatan-Leus et al, 2018), αναφέρεται αφενός μεν στον βασικό κανόνα της ψυχοδυναμικής θεραπείας για ελεύθερο συνειρμό από την πλευρά του θεραπευόμενου, αφετέρου δε στην αιωρούμενη προσοχή και δημιουργική ανταπόκριση από τον θεραπευτή (free-floating responsiveness) σε όσα ο θεραπευόμενος «φέρνει» στη θεραπεία. Σύγχρονοι θεωρητικοί (Parsons, 1999;Sandler, 2003;Schaefer & Greenberg, 1997) τονίζουν ότι η ικανότητα για «παιχνίδι» στη θεραπευτική σχέση είναι μια παράμετρος που εγγυάται τη δυνατότητα ανακατασκευής των πυρηνικών σχεσιακών μοντέλων του θεραπευόμενου, και γι' αυτό χρειάζεται να μελετηθεί περαιτέρω.…”
Section: αναπτυξιακές βάσεις της ψυχοδυναμικής θεραπευτικής σχέσηςunclassified
“…The key finding was that only one very recent study (Yonatan-Leus et al, 2018) Eleven studies (Bader, 1993;Bloomfield, 1980;Fabian, 2011;Grotjahn, 1971;Haig, 1986;Kennedy, 1991;Lusterman, 1992;Marcus, 1990;Poland, 1971;Schimel, 1978;Wright, 2000) were…”
Section: Measures and Therapy Outcomementioning
confidence: 99%